2002
DOI: 10.1093/hsw/27.3.193
|View full text |Cite
|
Sign up to set email alerts
|

One Last Pleasure? Alcohol Use among Elderly People in Nursing Homes

Abstract: The study discussed in this article describes the alcohol-related policies, practices, and problems experienced by a sample of 111 intermediate care facilities and homes for elderly people. Data were collected using a semi-structured telephone interview and indicate that alcohol use and associated problems among nursing home residents are common. Despite the problems reported, screening for alcohol problems among residents, treatment of identified problems, and training of staff were not found to be widespread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 0 publications
1
54
0
2
Order By: Relevance
“…), and few reported drinking because they wanted to, or because they liked drinking. This is consistent with previous research which demonstrated that, although pleasure has an obvious association with alcohol (Harrison, Kelly, Lindsay, Advocat, & Hickey, 2011;Klein & Jess, 2002), it is rarely included in prevention discourses, being undervalued as a primary catalyst for alcohol consumption (Bergmark, 2004). People often report enjoyment from drinking (Emslie et al, 2012), yet discourse around alcohol consumption nearly always includes a practical justification, for example to reward a hard day's work, or celebrate special occasions (Lyons, Emslie, & Hunt, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…), and few reported drinking because they wanted to, or because they liked drinking. This is consistent with previous research which demonstrated that, although pleasure has an obvious association with alcohol (Harrison, Kelly, Lindsay, Advocat, & Hickey, 2011;Klein & Jess, 2002), it is rarely included in prevention discourses, being undervalued as a primary catalyst for alcohol consumption (Bergmark, 2004). People often report enjoyment from drinking (Emslie et al, 2012), yet discourse around alcohol consumption nearly always includes a practical justification, for example to reward a hard day's work, or celebrate special occasions (Lyons, Emslie, & Hunt, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…Given the associations between alcohol use and demographic variables such as gender, age, race/ethnicity, marital status, education level, income, ever been homeless, and military status (Karlamangla et al, 2006;Myers et al, 2000;Sacco et al, 2009), we included these variables in our logistic regression model. Furthermore, given the established relationship between depression and alcohol use (Klein and Jess, 2002), as well as the potential negative health consequences associated with mixing alcohol with prescription medication (Breslow et al, 2003) or consuming alcohol with a diagnosis of diabetes, the logistic regression analysis included the GDS-s total score for each participant as well as whether the participant was currently taking prescription medication or had a diabetes diagnosis. We first tested the bivariate associations between the predictor variables and the outcome variable of alcohol use.…”
Section: Methodsmentioning
confidence: 99%
“…Males drink more frequently and in higher quantities than females (Breslow, Faden, & Smothers, 2003). Placement in AL may also be precipitated by problems associated with prior alcohol abuse or misuse (Klein & Jess, 2002).…”
Section: Assisted Living (Al)mentioning
confidence: 99%
“…Reports show that up to one half of nursing home residents suffer from alcohol problems (Klein & Jess, 2002). There is also a high number (36%) of elders in veterans' nursing homes who suffer from alcohol use disorders (Joseph et al, 1995).…”
Section: Alcohol Use Among Elders In Almentioning
confidence: 99%